Twelve month comparison of salmeterol and salbutamol as dry powder formulations in asthmatic patients. European Study Group. - Lundback, B (1993)
BACKGROUND: Salmeterol is a potent selective beta 2 agonist that has been shown to have a duration of action in excess of 12 hours. In this study salmeterol and salbutamol were compared over a three month period with a further extension of nine months. METHODS: Three hundred and eighty eight patients with mild to moderate reversible airways obstruction (forced expiratory volume in one second (FEV1) > 50% predicted) were randomised to receive salmeterol (50 micrograms) twice daily or salbutamol (400 micrograms) four times daily, both by dry powder, in a double blind parallel group study. During the first three months detailed assessment of efficacy was made with recording of morning and evening peak expiratory flow rates (PEF), asthma symptoms, and bronchodilator use when necessary for the relief of symptoms. Patients continued in the study for a further nine months with the salbutamol dose reduced to 400 micrograms twice daily. Lung function was measured at the clinic and safety data were collected during this period. RESULTS: Salmeterol produced a significantly higher mean morning PEF (mean difference compared with salbutamol 21 (95% CI 12-31) l/min), and a significant reduction in mean diurnal variation in PEF (from 30 l/min at baseline to 11 34 l/min at baseline to 32 l/min during salbutamol treatment). Salmeterol also reduced day and night symptoms and use of rescue bronchodilator. FEV1 increased with both salmeterol and salbutamol treatment over the 12 month treatment period. For both treatments the number of patients reporting exacerbations of asthma and the frequency of these exacerbations remained constant during the study. Thirty six patients in the salmeterol and 49 in the salbutamol group withdrew during the 12 months of the study. CONCLUSIONS: In this study salmeterol (50 micrograms twice daily) was more effective than salbutamol (400 micrograms four times daily) in the control of asthma over three months, and more effective than salbutamol (400 micrograms twice daily) over a further nine months. Neither salmeterol nor salbutamol was associated with any worsening of control of asthma.